Pengaruh Digital Marketing, Selebgram, dan Suasana Cafe Terhadap Minat Beli Coffee Shop Mojok Kopi Kota Malang - Rizki, Lutfi Andrian; Mustapita, Arini Fitria; Mahardani, Ahmad Subhan (UNIVERSITAS ISLAM MALANG, 2025)
Abstract The purpose of this research is to determine and test the partial and simultaneous influence of celebrities, digital marketing, and cafe atmosphere on intention to purchase coffee, Mojok Kopi in Malang City. Customers of coffee shops at Begawan Plaza, Malang City are the population of this study; the exact amount varies every day. with the help of the SPSS (Statistical package for social science) computer program. Purchasing interest is simultaneously influenced by digital marketing research findings, Instagram celebrities, and the cafe atmosphere. Purchase interest is not affected at all by digital marketing. Meanwhile, buying interest is somewhat influenced by the cafe atmosphere and Instagram celebrities. Keywords: Digital marketing, Celebrities, Cafe Atmosphere, and Purchase Interest.